2004
DOI: 10.1373/clinchem.2003.022459
|View full text |Cite
|
Sign up to set email alerts
|

The Interleukin-6 G(−174)C Promoter Polymorphism Does Not Determine Plasma Interleukin-6 Concentrations in Experimental Endotoxemia in Humans

Abstract: Background: Interleukin 6 (IL-6) is a pleiotropic cytokine that plays an essential role in the pathogenesis of acute and chronic infections. As the role of the IL-6 G(؊174)C polymorphism in determining serum concentrations of IL-6 is controversial, we studied the genotype-specific IL-6 response in a well-standardized model of systemic inflammation. Methods: A total of 76 healthy young males (age range, 19 -35 years) received a single bolus of 2 ng/kg endotoxin [lipopolysaccharide (LPS)] intravenously. Plasma I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0
3

Year Published

2005
2005
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 45 publications
2
42
0
3
Order By: Relevance
“…22 Indeed, the novel four-marker haplotype we describe here may only represent a partial elucidation of the complex regulation of IL-6, with additional upstream control regions remaining to be characterised. The IL-6 À174G4C, À572G4C, À1363G4T and À1480[CT] polymorphisms 23 In summary, our results clearly illustrate the importance of haplotypic analyses for disease associations, and that single SNP analyses are likely to provide contradictory results.…”
Section: Resultsmentioning
confidence: 98%
“…22 Indeed, the novel four-marker haplotype we describe here may only represent a partial elucidation of the complex regulation of IL-6, with additional upstream control regions remaining to be characterised. The IL-6 À174G4C, À572G4C, À1363G4T and À1480[CT] polymorphisms 23 In summary, our results clearly illustrate the importance of haplotypic analyses for disease associations, and that single SNP analyses are likely to provide contradictory results.…”
Section: Resultsmentioning
confidence: 98%
“…The CC genotype is considered to be a low producer and GG a high producer of IL-6 (4,7,8). However, Endler et al (6) did not find this association and Brull et al (9) found the opposite, i.e., patients with the CC allele had higher plasma IL-6 levels. Furthermore, other haplotypes cooperate with the transcriptional regulation of IL-6 influencing its production (10).…”
mentioning
confidence: 95%
“…It seems that the single-nucleotide polymorphism in the promoter region of the IL-6 gene at position -174 may regulate the plasma concentrations of IL-6 in vivo (4)(5)(6). The presence of lysine (allele C) at the guanine site (allele G) is associated with low levels of plasma IL-6 in healthy subjects.…”
mentioning
confidence: 99%
“…The control group (group T1) included eight patients with low trauma severity; their Injury Severity Score (ISS) was between 15-20. Ten patients with moderately severe trauma (ISS of [21][22][23][24][25][26][27][28][29][30] were enrolled in group T2. Group T3 consisted of 8 patients with very severe trauma (ISS > 30).…”
Section: Patientsmentioning
confidence: 99%